(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
This article examines a model for preparing future educational psychologists to effectively organize educational activities based on a systematic literature review. The study analyzes conceptual approaches from national, CIS, and international scholars, focusing on competency-based, activity-oriented, and learner-centered methods. The review highlights that integrating innovative pedagogical technologies with reflective and practical training significantly enhances the professional readiness of future educational psychologists for organizing educational activities.